'Moving in concentric circles'? The history and politics of press inquiries. (2nd January 2018) - Harker, Michael; Street, John; Cross, Samuel
Abstract : In this paper, we consider the Leveson inquiry's use of a narrative device – the policy cycle – to justify the need for a break with the past. We challenge that narrative, which runs through much of the literature, and posit a more nuanced and complex account of the politics and history of press inquiries, drawing upon the political science literature. We then reflect upon the implications of our findings for the future of press regulation.